St Paul the Apostle in the Ancient Legends of the Slavs and in the Literary Tradition of the Grand Duchy of Lithuania - Akushevich, Andrei; Menzel, Thomas; Nekrashevich-Karotkaya, Zhanna (Senoji Lietuvos literatūra, 2017)
Saint Paul the Apostle was mentioned in the baptism legends from the Early Middle Ages. In the Slavic context, the most in-demand legend was that of St Paul’s missionary work in Illyricum. First written down by Vuk Karadžić (1787–1864), the legend of shipwrecked Saint Paul, who lived in Dalmatia, was especially popular. Allusions to the acts of St Paul can also be found in the legends about Cyril-Constantine and Methodius as well as in the stories related to the earliest Eastern Slavic chronicles. The figure of St Paul never achieved the same symbolic importance in the East Slavic traditions that was attributed to the Apostle Andrew in the Eastern Church. But even St Paul gained a polemical weight in the seventeenth century (Patericon by Sylvester Kosiv) and was manipulated in the argument about the spheres of influence of the Western and Eastern churches.The Epistles of Paul had always enjoyed great popularity in the Christian homiletic discourse, not in the least due to the fact that excerpts from them were included in the liturgia verbi, and, consequently, played a significant role in the literary context of the Grand Duchy of Lithuania in the sixteenth-seventeenth centuries. The philological and exegetic work of Francysk Skaryna (1486–1551) relied heavily on the Epistles. According to some scholars, they indirectly lead to a new phenomenon in the early-printed books called a ‘preface–postface complex’. Pauline motives and allusions to the Epistles of Paul also form the basis of the moral and religious paradigm in the poem De vita et gestis divi Hyacinthi by Nicolaus Hussovianus (1480–1533). In the literature of the Reformation (Symon Budny, 1530–1593) and Counter-Reformation/Counter-Orthodoxy (Meletius Smotrytsky, 1577–1633; Leoncjusz Karpowicz, 1580–1620), the Epistles were usually quoted in the contexts of the dilemma of true/corrupt faith actively discussed by St Paul and of the problem of salvation through faith, in meditations about the nature of faith and in the theme of prophets and false prophets. Certain imageries created by Paul the Apostle (e. g., the divine triad of faith, hope, and love, the mystical body of Christ) were subject to multiple interpretations that laid the basis for a number of authentic artistic works.
Keywords: Saint Paul the Apostle; Epistles of St Paul; ancient legends of the Slavs; Cyril-Constantine and Methodius; ancient Bohemian legends; earliest Eastern Slavic chronicles; St Paul’s missionary work in Illyricum; literature of the Grand Duchy of Lithuania; Bible of Francysk Skaryna; De vita et gestis divi Hyacinthi by Nicolaus Hussovianus; Catechism of Symon Budny; sermons of Leoncjusz Karpowicz; the oeuvre by Meletius Smotrytsky; divine triad of faith, truth, and love; the mystical body of Christ